SIMPLIFIED MATHEMATICAL MODEL OF GROUP OF OVERHEAD POWER LINES MAGNETIC FIELD - B. I. Kuznetsov (National Technical University "Kharkiv Polytechnic Institute", 2020)
Aim. The method for design of simplified mathematical model of the group of overhead power lines magnetic field allowing to reduce the number of conductors which are taken into account in the model and field and allowing to reduce the sensitivity of the model to plant parameters uncertainty is developed. Methodology. The method based on the multi-criteria game decision, in which the payoff vector is calculated on the basis of the Maxwell equations quasi-stationary approximation solutions. The game decision based on the stochastic particles multiswarm optimization algorithms. The implementation of the method is carried out when determining the number, configuration, spatial arrangement and currents in conductors based on simplified mathematical model of the group of overhead power line magnetic field in a given space area. Results. Computer simulation and field experimental research results of simplified mathematical model on the example of the group of four overhead power lines magnetic field including 21 conductors where based on the developed simplified mathematical model of the magnetic field, the number of conductors taken into account in the model is reduced to 6, and the modeling error does not exceed 4 %. Originality. For the first time the method for design of simplified mathematical model of the group of overhead power lines magnetic field based on the stochastic particles multiswarm optimization algorithms, which allows to significantly simplify the simulation by reducing the number of conductors that are taken into account in the model and to reduce the sensitivity of the model to plant parameters uncertainty, and at the same time limit the modeling error at the engineering level to 5-10 %. Practical value. Practical recommendations on reasonable choice of the minimal number, configuration, spatial arrangement and currents in conductors for the simplified mathematical model of the group of overhead power line magnetic field.